Floristic characteristics of vascular plants in Qilian Mountain region, China - LI Jianan1,2,3, WANG Bo1,2,3, ZHAO Shuo1,2,3, ZHANG Famei1,2,3, ZHOU Guoying1,2 * (Guangxi Zhiwu)
Vegetation plays a crucial role in the terrestrial ecosystem and can serve as a valuable indicator of environmental change. Studying the flora is of importance for protection and utilization of plant resources. Furthermore, understanding the composition and distribution of vegetation not only enhances plant biodiversity and quality but also enables us to make scientific use of plant resources. The ecological transition zone, known for its high species diversity, is an essential area for studying the flora. Qilian Mountain region, as an ecological transition zone, exhibits high plant diversity. However, the flora composition in this area has not been systematically documented. In order to ensure the accuracy of the species list and explore the distribution of flora, we conducted preliminary statistics by collecting and organizing scattered data from the literature. Subsequently, we used the plant specimen information to proofread and determine the flora composition. The results were as follows:(1)Qilian Mountains region had 1 952 species of vascular plants, belonging to 108 families and 527 genera, including 44 species of national protected plants and 100 species of threatened plants.(2)The dominant plant types in Qilian Mountain region were herbaceous, followed by shrubs, with trees being the least abundant. Most of these plants exhibited cold-resistance and drought-tolerance, with the majority being oligotrophic genera(the genera containing only one plant in Qilian Mountain region). The geographical components of the flora were diverse, but the temperate elements were predominant.(3)Species richness was the highest in the eastern region of the mountain, followed by the middle region, and the lowest in the western region. As longitude increased westward, the similarity index decreased. This suggests that the species composition and geographical components are synthetically influenced by local climatic conditions, topographic conditions, and diverse habitat types.(4)The presence of endemic species was significant, with a total of 717 endemic species in China and 45 endemic species in Qilian Mountain region, reflecting the uniqueness, diversity, and complexity of the ecosystem in the important region. In short, the flora of Qilian Mountain region is characterized by youthfulness. As an ecological transition zone, the region has extremely rich plant species diversity and breeds a large number of rare plants. Due to the large longitude span of the Qilian Mountain region, there are great differences in plant types between the eastern and western regions. The above results provide background data and a scientific reference for the maintenance of species diversity, sustainable development, and utilization of resources in this area.